2019
DOI: 10.1108/aaaj-01-2018-3325
|View full text |Cite
|
Sign up to set email alerts
|

The question of research relevance: a university management perspective

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…The significance of various performance measures implemented by the government, regulatory bodies and universities cannot be underestimated (Martin-Sardesai et al, 2019). "Accountingisation", via the use of university PMSs at both the aggregate and individual levels, continues to be a technology in the exercise of management control and government oversight (Angluin and Scapens, 2000;Broadbent and Laughlin, 2013), particularly in terms of how these PMSs are used (Malina and Tucker, 2019), as well as their consequences (Tucker and Parker, 2019).…”
Section: The Theoretical Framework Of "Accountingisation"mentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of various performance measures implemented by the government, regulatory bodies and universities cannot be underestimated (Martin-Sardesai et al, 2019). "Accountingisation", via the use of university PMSs at both the aggregate and individual levels, continues to be a technology in the exercise of management control and government oversight (Angluin and Scapens, 2000;Broadbent and Laughlin, 2013), particularly in terms of how these PMSs are used (Malina and Tucker, 2019), as well as their consequences (Tucker and Parker, 2019).…”
Section: The Theoretical Framework Of "Accountingisation"mentioning
confidence: 99%
“…The second source of data [3] upon which this study draws is Tucker and Parker's recent interview-based investigation of the perceptions of senior research-related leaders (VCs, DVCs and research deans) about how research is operationalised within their universities (Tucker and Parker, 2019). In capturing their views, we provide the basis for identifying and evaluating assumptions underlying the development and implementation of PMSs, and the "accountingisation" of research from central players.…”
Section: Data Collectionmentioning
confidence: 99%
“…Over the last few decades, numerous studies have identified fundamental changes in academia that are typically connected to underlying assumptions concerning the nature of academia in general and how university organizations are managed in particular. Scholars with recent publications in interdisciplinary accounting journals include Gebreiter and Hidayah (2019), Kallio et al (2020), Lepori and Montanauti (2020), Tucker and Parker (2020), O'Connell et al (2020b), Conrath-Hargreaves and W€ ustemann (2019 and Gebreiter (2021). Scholars have typically recognized and theoretically elaborated on two or more competing logics.…”
Section: Competing Institutional Logics and Their Effects On Institutional Work In Academiamentioning
confidence: 99%
“…Over the last 30 years, institutional and socioeconomic development and globalization have played crucial roles in the changes observed in the higher education sector. These changes have affected aspects such as governance (Boitier and Rivi ere, 2013), accountability (Narayan et al, 2017), reputation (Suomi et al, 2014), higher education export (Guthrie et al, 2014), organization, funding, management (Tucker and Parker, 2020), budgeting (Lepori and Montauti, 2020;Mkasiwa, 2020), accounting systems (Conrath-Hargreaves and W€ ustemann, 2019;Moll and Hoque, 2011), research assessment (Martin-Sardesai et al, 2017a), as well as universities' academic and social legitimacy (Gebreiter and Hidayah, 2019). Previous studies have also shown clear changes occurring in the performance measurement (PM) of universities.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, the NPM approach taken by the government has steered the education sector through numerous reviews, policy reforms and changes in management accounting practices (Martin-Sardesai and Guthrie, 2018a; Guthrie et al , 2019; Martin-Sardesai et al , 2020), with universities forced to raise finance over and above government funding. National research assessment exercises have also been applied to the Australian HES since 2010, and have been used by universities to define how the university and academic research performance can be measured (Hicks, 2010, 2012; Evans, 2014; Martin-Sardesai et al , 2019; Tucker and Parker, 2020).…”
Section: Introductionmentioning
confidence: 99%